Web-Based Service Optimization with JSON-RPC Platform in Java and PHP - Wachyu Hari Haji (International Conference on Engineering and Technology Development (ICETD), 2012)
Web based application has been used by many organizations to support their business activities within the organization. Sometimes, that application requires the availability of information from other parties outside the organization. Other than that, there is a need to exchange information between applications in a particular organization with applications in other organizations. The applications may be on the different systems and platforms. There is a technology that can be used, commonly known as a web service. JSON-RPC is an alternative to build a web service. This technology involvestwoapplications that are connected via a data connection. During the connection, an application can executes a remote procedure from web service provider to do implementation web service using JSON-RPC technology, with PHP platform for client side application  and java platform for server side application.